ROLE OF URINARY CALCIUM CREATININE RATIO IN PREDICTION OF PREGNANCY INDUCED HYPERTENSION - DR. N.V. LAKSHMI MD,; DR.P.KIRANMAI MD,; DR.K.AMBIKA DEVI MD,; DR. J. RAMA RAO MD, (International Journal of Pharma and Bio Sciences, 2013)
Background: Preeclampsia occurring in 6-8% of all pregnancies together with other hypertensive disorders of pregnancy is the 3rd most common cause of maternal mortality. The present study is intended to identify at risk patients. Methods: Serum calcium, creatinine and urinary calcium, creatinine were estimated in 25 controls and 100 study group women between 24-34 weeks of gestation. Calcium to creatinine ratio in urine was calculated. The patients were followed up for signs of development of Pregnancy Induced Hypertension (PIH) & its relation to low urinary calcium to creatinine ratio (CCR). Results: A calcium to creatinine ratio of 0.04 was considered as cut off for evaluation. Out of total 125 cases, 22 had CCR £ 0.04 and of these 68.18% developed PIH later (P<0.001). In remaining 103 patients with CCR >0.04 only 4.85% had PIH. The sensitivity of CCR in predicting PIH is 68.18% and specificity is 95.15%. Conclusion: The findings indicate that a low Ca/Cr ratio is an useful screening test to predict the PIH in patients free of symptoms.